(untitled) (Veterinary Science, 2025)
The objective was to describe cardiological parameters in healthy canines and associate them with constitutive variables (age, sex and size). 178 animals were selected, age range 6.5 ±3.7 years, 81 males and 97 females, average weight 19.8 kg ±11.3 and average body condition 2.9 ±0.3. The sample was divided into 12 groups according to age (< 8 and > 8 years), sex (males and females) and size (< 12 kg, between 12 kg and 25 kg and > 25 kg). Systolic blood pressure (SBP), electrocardiographic, radiological and echocardiographic evaluation were determined in each canine. PAS had a mean of 146 mmHg ±20 mmHg, with no differences associated with sex/age/height. There were differences, for height, in P wave time and R deflection amplitude, the group < 12 kg presented 0.04 sec and 1.9 mv, between 12-25 kg 0.046 sec and 2.4 mv and > 25 kg 0.052 sec and 3.0 mv, respectively. The vertebral heart score (VHS) was 9.7 ±0.6, minimum 8.0 and maximum 11.2. The > 25 kg group showed higher VHS than other groups, with average values ​​greater than 10. The shortening, thickening and ejection fraction were 33% ±6%, 31% ±8% and 56% ±8%, respectively. No differences were evident in association with sex/age/height. The separation distance from point E to the septum had a maximum value of 7.1 mm; with gradual increase in relation to weight. The aorta/left atrium ratio had a mean of 1.06 ±0.12, with a maximum value of 1.26, showing no differences in relation to sex/age/height.